STUDY OF SOCIAL IMAGE RE-RANKING ACCORDING INTER AND INTRA USER IMPACT - Miss .Gaikwad Karuna B; Miss. Dagadkhair Priyanka V.; Miss .Patahare Varsha R; Miss. Aware Ashvini R (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Social media provides most of the websites for example Facebook that allows users to describe their images with special tag. That helps in the web image retrival system tag based image search is very important method to find out images uploaded by the social users in most of social websites that helps to make the result related and improve the variety of the images. we considered the visual information and click count of the images in this system first we sort the images by inter-user ranking the user who upload the maximum image will rank higher. After this we implement intra-user ranking on the ranked user image set and only the most related image from each user image database is selected . These selected images combine the final retrived results. We build an inverted index for social image databases to improve the speed of searching of an images.